Scaffolding CT via Point-And-Click and P5.js - Valente, Andrea; Marchetti, Emanuela; Abel, Edward (2023 14th IIAI International Congress on Advanced Applied Informatics (IIAI-AAI), 2023)
This paper investigates how to provide meaningful scaffolding to bachelor humanities students, to enabled them to acquire Computational Thinking (CT) technical skills, and in particular basic programming competences. Two of the authors have been involved in the re-design, implementation and execution of a basic programming and CT course, offered to first-semester students as part of the Information science, IT and interaction design bachelor program, at the University of Southern Denmark (SDU). The central problem we faced in restructuring our introductory course, was finding a game genre that could support creative coding for beginners, be motivational and recognizable by the students, and would work with our use-modify-create learning approach. Our findings suggest that point-and-click games are an effective way to provide scaffolding and ease non-technical students into P5 programming. The genre has good expressive power, and the students were motivated because they recognized and could relate to the games they worked on. Future work will address students' problems with scaling up the point-and-click games.